PENERAPAN PROGRAM LINIER DALAM MENGOPTIMALKAN KEBUTUHAN GIZI HARIAN BAYI USIA 7 BULAN SAMPAI 12 BULAN DENGAN BIAYA MINIMUM DI KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - -, Suriani; Afri, Lusi Eka; Deswita, Hera (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
Based on data obtained from the Department of Health Rokan Hulu malnourished baby 7 months-12 months are most at district Rambah Hilir. The purpose of the research was to establish a model of linear programs that met the daily needs of the baby 7 months-12 months, calculate the amount of food consumed at minimum cost, and analyze three cases combination that had been formed. After the calculation was did used the simplex method with the help of Qm For Windows, The optimum solution ware obtained from the three cases ware a combination of three cases of food. The combination of foodstuffs in the three cases ware as much as 82 grams of rice, tempeh as much as 268 grams, yellow squash as many as 100 grams and 99 grams of butter, and the minimum total cost incurred ware five thousand dollars every day.